2010
DOI: 10.1111/igc.0b013e3181c4a627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computed Tomography and Magnetic Resonance Imaging in Cervical Cancer Brachytherapy Target and Normal Tissue Contouring

Abstract: The CT- and MRI-based brachytherapy tissue delineation seems adequate for evaluation of OAR and target tissues, although the shapes of HR-CTV and OAR do differ. When adopting volume-based prescription, these differences may lead to altered target dosing. The clinical impact of these differences seems to be small and may demonstrate that planning with CT, if combined with one MRI, may be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
2
33
0
2
Order By: Relevance
“…[5,14] Contouring the target volumes based on CT images is limited, however, because CT cannot distinguish residual tumor extension from normal tissue, and it may overestimate the tumor volume. [15,16] Although both MRI and CT provide anatomical information, FDG-PET provides metabolic information about the glucose uptake of a tumor, which is correlated with the viable tumor burden. Thus, the metabolic tumor volume can be delineated using FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
“…[5,14] Contouring the target volumes based on CT images is limited, however, because CT cannot distinguish residual tumor extension from normal tissue, and it may overestimate the tumor volume. [15,16] Although both MRI and CT provide anatomical information, FDG-PET provides metabolic information about the glucose uptake of a tumor, which is correlated with the viable tumor burden. Thus, the metabolic tumor volume can be delineated using FDG-PET.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of image based brachytherapy and intensity-modulated radiotherapy can also improve dose distribution in target volume and overdose to organs at risk (Tharavichitkul et al, 2013). Few studies have concluded that in centers where MRI based brachytherapy is not feasible due to logistics reasons, OAR and target may be contoured with CT which gives comparable results to MRI for dose volume estimation if clinical findings and baseline MRI findings are applied in contouring of CT images (Eskander et al, 2010;Krishnatry et al, 2012 observed MRI is being used by 20% for planning (Gueda et al, 2010). The limitation of our study included small sample size and lack of MRI based brachytherapy planning as CT may have overestimated the clinical target volume as compared to MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional imaging modalities currently in use include computed tomography (CT) scan, and magnetic resonance imaging (MRI). MRI has been shown to be superior to CT in delineating gynecologic tumors and normal pelvic structures (19, 26, 3031). However, no study has compared clinical outcomes and quality of life indices of MR-based to CT-based ISBT for vaginal recurrence of EC.…”
Section: Introductionmentioning
confidence: 99%